Alzheimer's disease (AD) - Hodges, John (Henry Stewart Talks, 2007)
Basic epidemiological facts on AD, Typical and atypical symptoms, Cognitive and physical findings, Key clinical investigations typically undertaken, Broad therapeutic approaches, Natural history and prognosis
Archived at 2020/08/13